Fascism on the Theatrical Stage: Theatre as a Joyful Learning Approach to Japanese Occupation History - Mohamad Na’im; Jefri Rieski Triyanto; Mukhamad Zulianto; Dimas Anggoro (Paramita: Historical Studies Journal, 2026)
Abstract: This study examines the use of theatre during the Japanese occupation period as a medium for creating a more reflective and engaging history-learning experience. In many classrooms, the topic of the Japanese occupation in Indonesia is commonly taught through textbooks and teacher-centered explanations that emphasize political and economic aspects. As a result, cultural dimensions, such as the use of theatre as a propaganda tool during the occupation period, are rarely discussed in history education. This study aims to explore how theatre from the Japanese occupation era can be used as a pedagogical resource to help students understand the mechanisms of propaganda and power relations during that period. This research employed a qualitative case study approach involving 33 eleventh-grade students from a senior high school in Jember, Indonesia. Data were collected through classroom observations, semi-structured interviews with students, and document analysis of historical drama scripts used in classroom role-playing activities. The findings show that students initially had a limited understanding of theatre as a propaganda medium during the Japanese occupation. However, through role-playing activities, students recognized how performing arts were used to shape public opinion and communicate ideological messages. This study highlights the potential of arts-based learning in history education to deepen students’ historical understanding and foster critical awareness of propaganda in historical contexts. Abstrak: Penelitian ini mengkaji pemanfaatan teater pada masa pendudukan Jepang sebagai media untuk menciptakan pengalaman pembelajaran sejarah yang lebih reflektif dan menarik. Dalam banyak praktik pembelajaran di kelas, topik pendudukan Jepang di Indonesia umumnya diajarkan melalui buku teks dan penjelasan yang berpusat pada guru, dengan penekanan pada aspek politik dan ekonomi. Akibatnya, dimensi kultural seperti penggunaan teater sebagai alat propaganda pada masa pendudukan sering kali kurang mendapat perhatian dalam pembelajaran sejarah. Penelitian ini bertujuan untuk mengeksplorasi bagaimana teater pada masa pendudukan Jepang dapat dimanfaatkan sebagai sumber pedagogis untuk membantu siswa memahami mekanisme propaganda dan relasi kekuasaan pada periode tersebut. Penelitian ini menggunakan pendekatan studi kasus kualitatif yang melibatkan 33 siswa kelas XI dari sebuah sekolah menengah atas di Jember, Indonesia. Data dikumpulkan melalui observasi pembelajaran di kelas, wawancara semi-terstruktur dengan siswa, serta analisis dokumen berupa naskah drama sejarah yang digunakan dalam kegiatan role-playing di kelas. Hasil penelitian menunjukkan bahwa pada awalnya siswa memiliki pemahaman yang terbatas tentang teater sebagai media propaganda pada masa pendudukan Jepang. Namun, melalui kegiatan role-playing, siswa mampu memahami bagaimana seni pertunjukan digunakan untuk membentuk opini publik dan menyampaikan pesan ideologis. Penelitian ini menegaskan potensi pembelajaran berbasis seni dalam pendidikan sejarah untuk memperdalam pemahaman historis siswa sekaligus menumbuhkan kesadaran kritis terhadap propaganda dalam konteks sejarah.